Ion-conductive substance, electrolyte, and battery

By introducing specific compositions of ionic conductive substances into the halide solid electrolyte, the problem of insufficient ionic conductivity of the existing electrolyte is solved, and more efficient conductivity is achieved, which is suitable for battery applications.

CN119856235APending Publication Date: 2025-04-18SUMITOMO CHEM CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380064590.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-12
Filing Date
2023-09-07
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

There is still room for improvement in the ionic conductivity of existing halide solid electrolytes.

Method used

An ionic conductive substance including an alkali metal element, a quadrivalent metal element M, a halogen element, a dopant element X and an oxygen element is used. The content of the dopant element X is less than 50 mol% with respect to the content of the metal element M, and a specific X-ray diffraction peak is present at 25°C.

Benefits of technology

It significantly improves ionic conductivity, optimizes the performance of electrolytes, and is suitable for efficient battery applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856235A_ABST
    Figure CN119856235A_ABST
Patent Text Reader

Abstract

An ion-conductive substance containing an alkali metal element, a tetravalent metal element M, a halogen element, a dopant element X, and an oxygen element, the content of the dopant element X being 50 mol% or less with respect to the content of the metal element M. In an X-ray diffraction pattern obtained by measuring the ion-conductive substance using a CuK [alpha] ray at 25 DEG C, the content of the dopant element X is 50 mol% or less. And a diffraction peak having a half-value amplitude of 2.0-10 degrees within a 2 [theta] angle range of 10-20 degrees.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to ion conductive materials, electrolytes and batteries. Background Art

[0002] In recent years, solid electrolytes have attracted attention as electrolytes used in electrochemical devices such as lithium-ion batteries (Patent Documents 1 to 4). Solid electrolytes are superior to conventional electrolytes in high temperature durability and high voltage resistance, and are therefore considered useful for improving battery performance such as safety, high capacity, rapid charge and discharge, and battery pack energy density.

[0003] As described in Patent Documents 1 to 4, as materials used in solid electrolytes of lithium-ion batteries, solid electrolytes containing halides of lithium and metal elements other than lithium are known. Halide solid electrolytes have advantages that oxide-based or sulfide-based solid electrolytes do not have: they are highly flexible and therefore do not require sintering; they are highly safe because they do not release harmful substances such as H2S, etc.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2021002064

[0007] Patent Document 2: International Publication No. 2021024785

[0008] Patent Document 3: International Publication No. 2021220577

[0009] Patent Document 4: Japanese Patent No. 6947321 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, with regard to halide solid electrolytes, there is still room for improvement in ionic conductivity.

[0012] The present disclosure has been made in view of the above circumstances, and an object of the present disclosure is to provide an ion conductive material having excellent ion conductivity, and an electrolyte and a battery using the same.

[0013] Means for solving problems

[0014] The present disclosure includes the following embodiments [1] to [6].

[0015] [1] An ion conductive material comprising an alkali metal element, a tetravalent metal element M, a halogen element, a dopant element X and an oxygen element, wherein the content of the dopant element X is 50 mol % or less relative to the content of the metal element M, and wherein the ion conductive material has an X-ray diffraction pattern measured at 25°C using CuKα rays and has a diffraction peak with a half-value width of 2.0 to 10° within a range of 2θ angles of 10 to 20°.

[0016] [2] An ion conductive material comprising an amorphous phase and microcrystals dispersed in the amorphous phase, and containing an alkali metal element, a tetravalent metal element M, a halogen element, a dopant element X, and an oxygen element, wherein the average equivalent circle diameter of the microcrystals is less than 20 nm.

[0017] [3] The ion conductive material according to [1] or [2], wherein the dopant element is at least one of P and S.

[0018] [4] An ion conductive material according to any one of [1] to [3], wherein the content of alkali metal elements is 20 to 30 mol%, the content of metal elements M is 5 to 20 mol%, the content of halogen elements is 40 to 60 mol%, and the content of dopant element X is 0.05 to 5 mol%, relative to the total amount of atoms contained in the above-mentioned ion conductive material.

[0019] [5] An electrolyte comprising the ion conductive material according to any one of [1] to [4].

[0020] [6] A battery comprising the electrolyte described in [5].

[0021] Effects of the Invention

[0022] According to the present disclosure, it is possible to provide an ion conductive material having excellent ion conductivity, and an electrolyte and a battery using the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a figure which shows the X-ray diffraction pattern obtained about Examples 1-6 and Comparative Examples 1-3.

[0024] Figure 2 This is a graph showing Arrhenius curves obtained for the ion conductive materials of Examples 3, 5, and 6, and Comparative Examples 1 to 3.

[0025] Figure 3 This is a TEM image of the ion conductive material of Example 3.

[0026] Figure 4 It is a graph showing the results of cyclic voltammetry of Examples 1 to 5 and Comparative Example 1.

[0027] Figure 5 This is a graph showing the charge and discharge test results of Example 1. DETAILED DESCRIPTION

[0028] The ion conductive material (including alkali metal halide) of this embodiment contains an alkali metal element, a tetravalent metal element M (also referred to as element M), a halogen element, a dopant element X, and an oxygen element, and satisfies at least one of the following (1) and (2).

[0029] (1) The content of the dopant element X is 50 mol% or less relative to the content of the metal element M, and the ion conductive material has an X-ray diffraction pattern measured at 25°C using CuKα rays and has a diffraction peak with a half-value width of 2.0 to 10° within a range of 2θ angle of 10 to 20°.

[0030] (2) It contains an amorphous phase and crystallites dispersed in the amorphous phase, and the average particle size of the crystallites is 20 nm or less.

[0031] Regarding (1), the half width of the diffraction peak may be 4.0 to 9.0°, 4.5 to 8.8°, or 5.0 to 8.7°. It should be noted that in this specification, the half width refers to the full width at half maximum (FWHM) unless otherwise specified.

[0032] When (2) is satisfied, it can be said that the ion conductive material has a sea island structure. The average particle size of the microcrystals can be less than 15 nm, less than 10 nm, or less than 6 nm. In addition, it can be more than 1 nm, or more than 2 nm. The average particle size of the microcrystals can be, for example, the average value of the equivalent circle diameter calculated from the area of ​​the microcrystals in the microscope image obtained by a transmission electron microscope. The average can be the average of all crystals identified by the method described in the embodiment within the field of view (e.g., 188.6 nm×188.6 nm).

[0033] The alkali metal element contained in the ion conductive material of the present embodiment may be any one of Li, Na, K, Rb and Cs, but may include at least one of Li, Na and K, may include at least one of Li and Na, and may include Li.

[0034] Among the alkali metal elements contained in the ion conductive material, the ratio of one alkali metal element may be 80 mol % or more, 90 mol % or more, or 95 mol % or more. The one alkali metal element may be at least one of Li, Na, and K, at least one of Li and Na, or Li.

[0035] The content of the alkali metal element in the ion conductive material may be 20 to 30 mol %, 22 to 28 mol %, or 24 to 27 mol % relative to the total amount of atoms contained in the ion conductive material.

[0036] As the element M, Zr, Ti and Hf can be listed. The element M may contain at least one of Zr and Hf, and may contain Zr. The ion conductive material may contain one or more tetravalent metal elements M. The content of the tetravalent metal in the ion conductive material may be 5 to 20 mol%, 8 to 16 mol%, 8 to 15 mol%, or 9 to 13 mol% relative to the total amount of atoms contained in the ion conductive material. The element M may contain Zr and Hf. Among the tetravalent metal elements contained in the ion conductive material, the content of Zr may be 70 mol% or more, 80 mol% or more, 85 mol% or more, or 90 mol% or more. Among the tetravalent metal elements contained in the ion conductive material, the content of Zr may be 99.9 mol% or less, 99 mol% or less, 98 mol% or less, 97 mol% or less, or 95 mol% or less.

[0037] The ion conductive material may contain a metal element M2 other than a tetravalent metal (excluding alkali metal elements). The metal element M2 may be at least one of a divalent, trivalent or pentavalent metal element. As a divalent metal, alkaline earth metals, Zn, etc. may be listed. As a trivalent metal element, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Y, Al, Ga, In, Bi and Sb may be listed. As a pentavalent metal element, Nb and Ta may be listed. As an alkaline earth metal, it may be at least one of Mg, Ca, Sr and Ba, it may be at least one of Mg and Ca, or it may be Mg. The content of M2 may be 30 mol% or less, 20 mol% or less, 15 mol% or less, or 10 mol% or less relative to the total amount of metal elements other than alkali metals contained in the ion conductive material (the total amount of element M and element M2). The content of M2 can be greater than 0.1 mol%, greater than 1 mol%, greater than 2 mol%, greater than 2 mol%, greater than 3 mol%, or greater than 5 mol%, relative to the total amount of divalent to tetravalent metal elements contained in the ion conductive material.

[0038] The halogen element contained in the ion conductive material of this embodiment may be any one of F, Cl, Br and I, but may contain at least one of Cl, Br and I, may contain at least one of Cl and Br, or may contain Cl. The ion conductive material may contain only one halogen element, but may contain two or more halogen elements.

[0039] The content of the halogen element in the ion conductive material may be 40 to 60 mol %, 43 to 55 mol %, or 45 to 52 mol % relative to the total amount of atoms contained in the ion conductive material.

[0040] The dopant element X contained in the ion conductive material of the present embodiment may be an element that can form a tetrahedral structure XO4 with four oxygen atoms, and may be at least one of P and S. The dopant element X may include P. Alternatively, the dopant element X may include S.

[0041] The content of the dopant element X in the ion conductive material may be 0.05 to 5 mol %, 0.1 to 3 mol %, 0.2 to 2 mol %, or 0.3 to 1 mol % relative to the total amount of atoms contained in the ion conductive material.

[0042] The content of the dopant element X in the ion conductive material may be 50 mol% or less, 1 to 30 mol%, 1 to 20 mol%, or 2 to 10 mol% of the content of the tetravalent metal element M. The content of the dopant element X in the ion conductive material may be 20 mol% or less, 15 mol% or less, 10 mol% or less, or 8 mol% or less of the content of the tetravalent metal element M.

[0043] The content of the dopant element X in the ion conductive material may be 1 to 10 mol % of the content of the oxygen element, or may be 2 to 6 mol %.

[0044] The content of oxygen in the ion conductive material may be 5 to 20 mol %, 8 to 18 mol %, or 10 to 16 mol % relative to the total amount of atoms contained in the ion conductive material.

[0045] The ion conductive material of the present embodiment may contain a compound represented by the following composition formula (1) (also referred to as an alkali metal halide compound).

[0046] A α M β X γ Z δ E η O ε (1)

[0047] (In the formula, A is an alkali metal element, M is the above-mentioned tetravalent metal element M, X is the above-mentioned dopant element X, Z is a halogen element, 1.5≤α≤3, 0.5≤β≤2, 0.005≤γ≤0.5, 3≤δ≤6, 0.5≤ε≤2.)

[0048] α may be 1.8≤α≤2.5, 1.9≤α≤2.3, or 1.95≤α≤2.2. The upper limit and the lower limit of α may be arbitrarily combined.

[0049] β may be 0.7≤β≤1.4, 0.8≤β≤1.2, or 0.9≤β≤1.1. The upper limit and the lower limit of β may be arbitrarily combined.

[0050] γ may be 0.01≤γ≤0.2, 0.02≤γ≤0.15, or 0.025≤γ≤0.10. The upper limit and the lower limit of γ may be arbitrarily combined.

[0051] δ may be 3.5≤δ≤5, 3.7≤δ≤4.3, or 3.8≤δ≤4.1. The upper limit and the lower limit of δ may be arbitrarily combined.

[0052] ε may be 0.7≤ε≤1.5, 0.8≤ε≤1.3, or 0.9≤ε≤1.2. The upper limit and the lower limit of ε may be arbitrarily combined.

[0053] E may be an element other than A, M, X, Z and O, and may be an element added or mixed in addition to the essential elements. Examples of E include C, B, and N. η may be 0 to 0.1, 0 to 0.01, 0 to 0.001, or substantially 0.

[0054] Furthermore, the ion conductive material of the present embodiment may contain a compound represented by the following composition formula (2) (also referred to as an alkali metal halide compound).

[0055] A α M β M 2 ζ X γ Z δ E η O ε (2)

[0056] (wherein A is an alkali metal element, M is the tetravalent metal element M mentioned above, and M 2 M is a metal element other than tetravalent 2 (Except for alkali metal elements), X is the above-mentioned dopant element X, and Z is a halogen element.)

[0057] Preferred ranges for α, β, γ, δ, and ε in formula (2) may be the same ranges as those exemplified as the ranges for α, β, γ, δ, and ε in formula (1).

[0058] ζ may be 0.01≤ζ≤0.3, 0.03≤ζ≤0.2, or 0.05≤ζ≤0.15. The upper limit and the lower limit of ζ may be arbitrarily combined.

[0059] E can be A, M, M 2 , X, Z and O, and is an element added or mixed in addition to the essential elements. Examples of E include C, B, and N. η may be 0 to 0.1, 0 to 0.01, 0 to 0.001, or substantially 0.

[0060] The activation energy of the ion conductive material of the present embodiment may be 0.35 eV or less, 0.33 eV or less, or 0.23 to 0.35 eV. The activation energy of the ion conductive material may be determined by measuring the ion conductivity σ at 5 points (25°C, 40°C, 60°C, 80°C, and 100°C) in the temperature range of 25°C to 100°C, and performing curve fitting based on the following calculation formula.

[0061] Formula: σT=Aexp(-E a / k b T)

[0062] Where σ represents ionic conductivity (S / cm), T represents absolute temperature (K), A represents frequency factor, and E a represents the activation energy, k b represents the Boltzmann constant.

[0063] Furthermore, a graph (Alineus curve) can be prepared in which σ is taken as the vertical axis and 1000 / T (T is absolute temperature) is taken as the horizontal axis.

[0064] The method for producing the ion conductive material according to the present embodiment is not particularly limited, and an example thereof includes a method comprising a step of ball-milling a raw material.

[0065] As raw materials, there is no particular limitation. For example, as alkali metal sources, alkali metal halides, alkali metal oxides, etc. can be listed. As metal element M sources, halides of metal element M can be listed. As metal element M2 sources, halides of metal element M2 can be listed. As dopant element X sources, compounds such as salts of XO4 ions and alkali metals can be listed. The raw materials are preferably mixed before ball milling, and more preferably mixed under an inactive atmosphere (e.g., Ar atmosphere).

[0066] The ball milling conditions are not particularly limited, but may be set to a rotation speed of 200 to 700 rpm for 10 to 100 hours. The pulverization time may be 1 to 72 hours, 12 to 60 hours, or 20 to 60 hours.

[0067] The balls used in the ball mill are not particularly limited, but zirconia balls can be used. The size of the balls used is not particularly limited, but balls of 2 mm to 10 mm can be used.

[0068] By performing ball milling for the above-mentioned time, the raw materials are sufficiently mixed, and the mechanochemical reaction is promoted, thereby improving the ion conductivity of the obtained compound.

[0069] It is preferred that the product (ion conductive material) obtained by ball milling is not annealed. If annealing is performed, the crystallites may grow and become coarse, and the above-mentioned effect cannot be obtained. As annealing, for example, heating the ball milled product at 100° C. or above, 150° C. or above, or 200° C. or above can be cited.

[0070] The ion conductive material of the present embodiment can be used as a material for electrochemical devices such as capacitors and batteries. As such a material, for example, an electrolyte (solid electrolyte) material can be cited. As a battery, a lithium ion battery, a sodium ion battery, etc. can be cited as a battery that charges and discharges by moving alkali metal ions between the positive electrode and the negative electrode. In addition, the ion conductive material of the present embodiment can also be contained in the positive electrode or the negative electrode of the battery.

[0071] Hereinafter, the battery of this embodiment is described by taking a lithium ion battery as an example. The lithium ion battery includes a positive electrode and a negative electrode and an electrolyte (solid electrolyte) disposed between the positive electrode and the negative electrode. The ion conductive material (containing an alkali metal halide (in this case, a lithium halide)) of this embodiment can be contained in the electrolyte of the lithium ion battery.

[0072] The positive electrode of the lithium ion battery is not particularly limited, and may be a positive electrode containing a positive electrode active material and, if necessary, a conductive auxiliary agent, a binder, and the like.

[0073] The positive electrode may be a positive electrode having a layer containing these materials formed on a current collector. Examples of positive electrode active materials include lithium (Li) and at least one transition metal selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, and Cu. Examples of such lithium composite metal oxides include LiCoO2, LiNiO2, LiMn2O4, Li2MnO3, LiNi x Mn y Co 1-x-y O2[0 <x+y<1])、LiNi x Co y Al 1-x-y O2[0 <x+y<1])、LiCr 0.5 Mn 0.5O2, LiFePO4, Li2FeP2O7, LiMnPO4, LiFeBO3, Li3V2(PO4)3, Li2CuO2, Li2FeSiO4, Li2MnSiO4, etc.

[0074] The negative electrode of the lithium ion battery is not particularly limited, and may be a negative electrode containing a negative electrode active material and, if necessary, a conductive auxiliary agent, a binder, etc. For example, single substances such as Li, Si, P, Sn, Si-Mn, Si-Co, Si-Ni, In, Au, and alloys or composites containing these elements, carbon materials such as graphite, and materials in which lithium ions are embedded between the layers of the carbon materials, etc. may be cited.

[0075] The material of the current collector is not particularly limited and may be a single substance or an alloy of a metal such as Cu, Mg, Ti, Fe, Co, Ni, Zn, Al, Ge, In, Au, Pt, Ag, or Pd.

[0076] The solid electrolyte layer may have a plurality of layers. For example, a sulfide solid electrolyte layer may be provided in addition to the solid electrolyte layer containing the ion conductive material of the present embodiment. A sulfide solid electrolyte layer may also be provided between the solid electrolyte containing the ion conductive material of the present embodiment and the negative electrode. The sulfide solid electrolyte is not particularly limited, but examples thereof include Li6PS5Cl, Li2S-PS5, Li 10 GeP2S 12 , Li 9.6 P3S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li3PS4, etc.

[0077] Example

[0078] (Example 1)

[0079] ·ball milling

[0080] In an argon atmosphere having a dew point of -70°C or less (hereinafter referred to as a dry argon atmosphere), 0.1334 g of Li2O, 1.0407 g of ZrCl4, and 0.0259 g of Li3PO4 were weighed to prepare raw materials.

[0081] The above raw materials were placed in a 50 ml zirconia container for planetary ball milling, and 65 g of zirconia balls with a diameter of 4 mm were added, and the mixture was treated by mechanochemical reaction at 300 rpm for 24 hours to obtain the ion conductive material of Example 1.

[0082] The ball mill was carried out in a mode where the rotation direction was alternately switched between clockwise and counterclockwise, with the ball mill rotating for 10 minutes and stopping for 1 minute at intervals. The feed composition of the obtained ion conductive material (containing lithium chloride) was Li 2.15 ZrCl4О(PО4) 0.05 .

[0083] Planetary ball mill: PM400 manufactured by Verder Scientific Co., Ltd.

[0084] (Example 2)

[0085] An ion conductive material was produced in the same manner as in Example 1 except that ball milling was performed for 48 hours.

[0086] (Example 3)

[0087] An ion conductive material was produced in the same manner as in Example 1 except that the mixing ratio of the raw materials was changed so as to have the charging composition shown in Table 2.

[0088] (Example 4)

[0089] An ion conductive material was produced in the same manner as in Example 1 except that Li 2 SO 4 was used instead of Li 3 PO 4 and the mixing ratio of the raw materials was changed so as to obtain the charging composition shown in Table 2.

[0090] (Example 5)

[0091] As raw materials, Li2O, ZrCl4, HfCl4 and Li3PO4 were used, and the mixing ratio of the raw materials was changed so as to obtain the charging composition shown in Table 2. The ion conductive material was produced in the same manner as in Example 1.

[0092] (Example 6)

[0093] As raw materials, Li2O, ZrCl4, MgCl2 and Li3PO4 were used, and the mixing ratio of the raw materials was changed so as to obtain the charging composition shown in Table 2. Except for this, the ion conductive material was produced in the same manner as in Example 1.

[0094] (Example 7)

[0095] As raw materials, Li2O, ZrCl4, MgCl2 and Li3PO4 were used, and the mixing ratio of the raw materials was changed so as to obtain the charging composition shown in Table 2. Except for this, the ion conductive material was produced in the same manner as in Example 1.

[0096] (Comparative Example 1)

[0097] An ion conductive material was produced in the same manner as in Example 1 except that LiCl and ZrCl 4 were used as raw materials and the mixing ratio of the raw materials was changed so as to have the charging composition shown in Table 2.

[0098] (Comparative Example 2)

[0099] As raw materials, LiCl, Li2O and ZrCl4 were used, and the mixing ratio of the raw materials was changed so as to obtain the charging composition shown in Table 2. An ion conductive material was produced in the same manner as in Example 1.

[0100] (Comparative Example 3)

[0101] An ion conductive material was produced in the same manner as in Example 1 except that Li2O and ZrCl4 were used as raw materials and the blending ratio was adjusted to obtain the feed composition shown in Table 2 and the obtained product was annealed at 200°C for 5 hours.

[0102] (Comparative Example 4)

[0103] An ion conductive material was produced in the same manner as in Example 1 except that Li 2 SO 4 was used instead of Li 3 PO 4 and the mixing ratio of the raw materials was changed so as to obtain the charging composition shown in Table 2.

[0104] <Powder X-ray Diffraction>

[0105] The obtained ion conductive material was evaluated for diffraction peaks observed in the range of 10 to 20° in terms of 2θ by powder X-ray diffraction measurement at 25° C. The results are shown in Table 2. The powder X-ray diffraction measurement was carried out under the following conditions.

[0106] Measuring device: Ultima IV (manufactured by Rigaku Co., Ltd.)

[0107] X-ray generator: CuKα ray source voltage 40kV, current 40mA

[0108] X-ray detector: scintillation counter or semiconductor detector

[0109] Measurement range: Diffraction angle 2θ = 5° to 80°

[0110] Scanning speed: 4° / min

[0111] Figure 1 It is a figure which shows the X-ray diffraction pattern obtained about the ion conductive material of Examples 1-6 and Comparative Examples 1-3.

[0112] The half-value width of the peak was determined by removing the background signal and performing fitting.

[0113] <Evaluation of ionic conductivity>

[0114] A press forming die having a frame die, a punch lower portion, and a punch upper portion was prepared. It should be noted that the frame die was formed of insulating polycarbonate. In addition, the punch upper portion and the punch lower portion were both formed of electronically conductive stainless steel and were electrically connected to the terminals of an impedance analyzer (S11260 manufactured by Solatron Analytical Co., Ltd.).

[0115] The ionic conductivity of the ionic conductive material is measured by the following method using the above-mentioned pressure forming mold. First, in a dry argon atmosphere, the powder of the ionic conductive material is filled into the lower part of the punch inserted into the hollow part of the frame mold from the vertical bottom. Then, by pressing the upper part of the punch into the hollow part of the frame mold from the top, a pressure of 370MPa is applied to the powder of the ionic conductive material inside the pressure forming mold. After the pressure is applied, the punch is tightened and fixed from the top and bottom with a clamp, and the impedance of the ionic conductive material is measured by electrochemical impedance spectroscopy using the above-mentioned impedance analyzer while maintaining a certain pressure.

[0116] The impedance measurement results were used to create a Cole-Cole line graph. In the Cole-Cole line graph, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the ion conductive material relative to ion conduction. Using this resistance value, the ion conductivity is calculated based on the following mathematical formula (III). The results are shown in Table 2.

[0117] σ=(R SE ×S / t) -1 (III)

[0118] in,

[0119] σ is the ionic conductivity,

[0120] S is the contact area between the ion conductive material and the upper part of the punch (equal to the cross-sectional area of ​​the hollow part of the frame mold),

[0121] R SE is the resistance value of the solid electrolyte material in impedance measurement,

[0122] t is the thickness of the ion conductive material when pressure is applied.

[0123] The ionic conductivity at 25°C was measured. In addition, the ionic conductivity was measured at 5 points (25°C, 40°C, 60°C, 80°C and 100°C) in the temperature range of 25°C to 100°C. The results are shown in Table 2. It should be noted that the ionic conductivity at each of the five temperature points is represented by σ T(T = 25°C, 40°C, 60°C, 80°C or 100°C). Figure 2 Graph showing the Alineus curves obtained for the ion conductive materials of Examples 3, 5 and 6 and Comparative Examples 1 to 3. Figure 2 , the two points where the value of 1000 / T in Example 6 is the smallest almost overlap with the two points where the value of 1000 / T in Example 3 is the smallest.

[0124] <Microstructure Observation Using a Transmission Electron Microscope>

[0125] Equipment: Analytical electron microscope ARM200F, manufactured by JEOL Ltd.

[0126] Measurement conditions: Acceleration voltage 200 kV

[0127] Sample conditioning: Processing in an inert atmosphere while cooling with a cryostat using a focused ion beam (FIB)

[0128] Figure 3 The TEM image of the ion conductive material of Example 3 is shown in FIG. Figure 3 As shown in , it is known that an island structure is formed in which the island structure is the crystalline phase and the sea structure of the amorphous phase is formed in a manner of surrounding the island structure. Here, in the electron diffraction pattern obtained by observation with a transmission electron microscope, by imaging the crystal whose diffraction spot exists within the aperture that limits the field of view, the crystal corresponding to the specific diffraction spot can be imaged brighter than the surrounding amorphous phase in real space. In this way, the distribution of the crystalline phase in real space is known. Figure 3 In the figure, the part surrounded by the white circle is the crystalline phase.

[0129] exist Figure 3 In the image, the image is colored so that the brightly imaged portion becomes clear, and each crystal phase is numbered. In this way, the spatial distribution of the crystal phase was investigated.

[0130] Furthermore, as to the crystal phase, a total of 51 crystal grains in the field of view in the figure were analyzed, and the average circle-equivalent diameter of the crystal phase was 4.5 nm.

[0131] <Fabrication of Cells for Cyclic Voltammetry>

[0132] The cyclic voltammetry cell was produced as described below. The cyclic voltammetry cell was produced in a glove box replaced with an inert gas.

[0133] First, the ion conductive material of Example 1 was placed in an insulating cylinder having an inner diameter of 10 mm. A pressure of 370 MPa was applied to the ion conductive material to form a solid electrolyte layer (layer of the ion conductive material).

[0134] Next, 60 mg of In foil was placed in contact with and cover the solid electrolyte layer, and 2 mg of Li foil was placed in contact with and cover the In foil to obtain a stacked body. A pressure of 370 MPa was applied to the stacked body to form a reference electrode made of a Li-In alloy on the solid electrolyte layer.

[0135] Furthermore, a disc-shaped plate made of stainless steel with a diameter of 10 mm and a thickness of 0.1 mm was arranged in contact with and covering the first solid electrolyte layer to obtain a laminated body. A pressure of 370 MPa was applied to the obtained laminated body to form a working electrode made of stainless steel on the solid electrolyte layer.

[0136] A current collector made of stainless steel was mounted on the reference electrode and the working electrode, and then a lead was mounted on the current collector. All components were placed in a sealed desiccator in a glove box. Thus, a cell for cyclic voltammetry was obtained.

[0137] <Cyclic Voltammetry Test>

[0138] For the above-mentioned cyclic voltammetry cell, the reference electrode and the working electrode were electrically connected to an impedance analyzer S11260 and a potentiostat S11287A, and a cyclic voltammetry test was carried out under the following conditions.

[0139] That is, in the cyclic voltammetry test, the scan rate is set to 1 mV / s and the voltage relative to the reference electrode (Li + The current value that flows when the potential of the working electrode is changed by using the Li-In ( / Li-In) electrode.

[0140] First, the potential of the working electrode was raised to 5.5 V with respect to the reference electrode from the open circuit voltage as a starting point, then turned back and dropped to 0 V.

[0141] The cyclic voltammetry test was performed at room temperature (25° C.). The potential at which a reduction current of 0.5 μA or more was observed was measured and used as an index of electrochemical stability. The results are shown in Table 2.

[0142] Figure 4 It is a graph showing the results of cyclic voltammetry of Examples 1 to 5 and Comparative Example 1. Compared with Comparative Example 1, the potential window of the ion conductive materials of Examples 1 and 2 is expanded to the lower potential side, and it can be said that the stability is improved.

[0143] In a dry argon atmosphere, 29 parts by mass, 67 parts by mass, and 4 parts by mass of the ion conductive material of Example 6 and LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, and acetylene black are mixed in a mortar to obtain a mixture.

[0144] In an insulating cylinder with an inner diameter of 10 mm, 100 mg of the ion conductive material of Example 1 and 15 mg of the above mixture were stacked in sequence to obtain a stacked body. A pressure of 370 MPa was applied to the stacked body to form the first electrode (layer of the above mixture) and the first solid electrolyte layer (layer of the above ion conductive material).

[0145] Next, 60 mg of sulfide solid electrolyte Li6PS5Cl was added to the first solid electrolyte layer in such a manner as to make it contact, thereby obtaining a laminate. A pressure of 370 MPa was applied to the laminate to form a second solid electrolyte layer. The first solid electrolyte layer was sandwiched between the first electrode and the second solid electrolyte layer.

[0146] Next, 60 mg of In foil was placed in contact with the second solid electrolyte layer, and 2 mg of Li foil was placed in contact with the In foil to obtain a laminated body. A pressure of 370 MPa was applied to the laminated body to form a second electrode.

[0147] A current collector made of stainless steel was attached to the first electrode and the second electrode, and then a lead was attached to the current collector. All components were placed in a desiccator and sealed, thereby obtaining the secondary battery of Example 1.

[0148] <Charge and discharge test>

[0149] The test was carried out using the following product as a charge and discharge tester.

[0150] Charge and discharge tester: Toyo System Co., Ltd. TOSCAT-3100

[0151] The charge and discharge test was carried out at 25° C. at three C rates of 0.1C, 1C, and 3C.

[0152] The discharge capacities at various C rates are shown in Table 1.

[0153] The battery was charged to 3.7 V at a current density corresponding to each C rate using constant current constant voltage (CCCV charging). Table 1 shows the current density corresponding to each C rate.

[0154] For discharge, the battery was discharged to 1.9 V at a current density corresponding to each C rate.

[0155] Figure 5. The charge and discharge test results of Example 1 are shown in FIG. 1 , and the discharge capacity of Example 1 at each C rate is shown in Table 1 .

[0156] In Example 1, a high discharge capacity was obtained at any C rate.

[0157] [Table 1]

[0158] Discharge capacity (unit: mAh / g)

[0159]

[0160] Discharge capacity (unit: mAh / g)

[0161]

Claims

1. An ion conductive material comprising an alkali metal element, a tetravalent metal element M, a halogen element, a dopant element X and an oxygen element, wherein the content of the dopant element X is 50 mol % or less relative to the content of the metal element M, The ion conductive material has a diffraction peak with a half-value width of 2.0 to 10° in a range of 2θ angle of 10 to 20° in an X-ray diffraction pattern measured at 25°C using CuKα rays.

2. An ion conductive material comprising an amorphous phase and microcrystals dispersed in the amorphous phase, and containing an alkali metal element, a tetravalent metal element M, a halogen element, a dopant element X and an oxygen element, The average equivalent circle diameter of the microcrystals is 20 nm or less.

3. The ion conductive material according to claim 1 or 2, wherein The dopant element is at least one of P and S.

4. The ion conductive material according to claim 1 or 2, wherein Relative to the total amount of atoms contained in the ion conductive substance, The content of alkali metal elements is 20 to 30 mol%. The content of metal element M is 5 to 20 mol%. The content of halogen elements is 40 to 60 mol%. The content of the dopant element X is 0.05 to 5 mol %. 5 . An electrolyte comprising the ion conductive substance according to claim 1 . A battery comprising the electrolyte according to claim 5 .

Citation Information

Patent Citations

  • Battery

    WO2021002064A1

  • Solid electrolyte, solid electrolyte layer, and solid electrolyte cell

    WO2021024785A1

  • Solid electrolyte material and battery using same

    WO2021220577A1